Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, December 3, 1929 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1929)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, December 03, 1929. Warner agreed promptly to the arrangement, for on November 14th, 1859 less than two weeks later, Hawley wrote acknowledging an article. Warner apparently was giving serious thought of the possibility of eventually coming to Hartford and joining Hawley on the Press. Hawley was delighted at the idea, of course. On November 14th, Hawley wrote to Warner about politics regarding Abraham Lincoln, his opponent and their famous debates.
1 electronic record. Scanned newspaper article. 2 image scans. 846 KB (866,612 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 27.8 MB (29,185,917 bytes)
Keywords: United States--History--Civil War, 1861-1865; Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); Personal correspondence; Letters; Newspapers